False‐Name Manipulation in Weighted Voting Games: Empirical and Theoretical Analysis*. (5th July 2016) - Lasisi, Ramoni O.; Allan, Vicki H.
Abstract : Weighted voting games are important in multiagent systems because of their usage in automated decision making. However, they are not immune from the vulnerability of false‐name manipulation by strategic agents that may be present in the games. False‐name manipulation involves an agent splitting its weight among several false identities in anticipation of power increase. Previous works have considered false‐name manipulation using the well‐known Shapley–Shubik and Banzhaf power indices. Bounds on the extent of power that a manipulator may gain exist when it splits into k = 2 false identities for both the Shapley–Shubik and Banzhaf indices. The bounds when an agent splits into k > 2 false identities, until now, have remained open for the two indices. This article answers this open problem by providing four nontrivial bounds when an agent splits into k > 2 false identities for the two indices. Furthermore, we propose a new bound on the extent of power that a manipulator may gain when it splits into several false identities in a class of games referred to as excess unanimity weighted voting games. Finally, we complement our theoretical results with empirical evaluation. Results from our experiments confirm the existence of beneficial splits into several false identities for the two indices, and also establish that splitting into more than two false identities is qualitatively different than the previously known splitting into exactly two false identities.